Evolutionary conservation of nested MIR159 structural microRNA genes and their promoter characterization in Arabidopsis thaliana - Imran, Muhammad; Liu, Tengfei; Wang, Zheng; Wang, Min; Liu, Shulin; Gao, Xinyan; Wang, Anning; Liu, Songfeng; Tian, Zhixi; Zhang, Min (Frontiers in Plant Science, 2022)
MicroRNAs (miRNAs) are endogenous small RNAs, and vital for gene expression regulation in eukaryotes. whenever a pri-miRNA precursor includes another miRNA precursor, and both of these precursors may generate independent non overlapping mature miRNAs, we named them nested miRNAs. However, the extent of nested miR159 structural evolutionary conservation and their promoter characterization remains unknown. In this study, the sequence alignment and phylogenetic analysis reveal that the MIR159 family is ancient, and its nested miR159 structures were evolutionary conserved in different plant species. The overexpression of ath-MIR159a including 1.2 kb downstream region of has no effect on rescuing the mir159ab phenotype. The promoter truncation results revealed that the 1.0 kb promoter of ath-MIR159a is sufficient for rescuing the mir159ab phenotype. The cis-regulatory elements in the ath-miR159a promoters indicated functions related to different phytohormones, abiotic stresses, and transcriptional activation. While the MybSt1 motif-containing region is not responsible for activating the regulation of the miR159a promoter. The qRT-PCR results showed that overexpression of ath-MIR159a lead to in high expression levels of miR159a.1–5 and miR159a.1–3 and complemented the growth defect of mir159ab via downregulation of MYB33 and MYB65. Furthermore, continuously higher expression of the miR159a.2 duplex in transgenic lines with the curly leaf phenotype indicates that miR159a.2 is functional in Arabidopsis and suggests that it is possible for a miRNA precursor to encode several regulatory small RNAs in plants. Taken together, our study demonstrates that the nested miR159 structure is evolutionary conserved and miRNA-mediated gene regulation is more complex than previously thought.